Perceived Social Support and Stress among Pregnant Women at Health Centers of Iran- Tabriz - Iranzad, Ilnaz (J Caring Sci, 2014)
Introduction: Social support is considered the interaction between the person and environment, which reduces stressors, covers the effects of stress and consequently protects individuals from the harmful effects of stressful situations. This study aimed to determine social support in pregnant women and its relationship with the rate of pregnant women's perceived stress at health centers of Tabriz in 2012-13. Methods: This cross-sectional study was carried out on 450 pregnant women selected through cluster sampling. Data collection tools consisted of a demographic questionnaire, interpersonal support evaluation list (ISEL) and perceived stress questionnaire (PSS) that were completed in an interview. The range of obtainable score for social support and perceived stress was 0-90 and 0-30, respectively. Descriptive and analytical statistics including Pearson and Independent t-test were used for analyzing the data. Results: The mean score of social support and perceived stress in pregnant women was 96.6 (14.6), and 11.5 (5.5), respectively .The women with favorable social support had significantly less stress than the women with unfavorable social support. Conclusion: The study finding showed that the rate of social support in highly stressful women is significantly less than low-stress mothers. Therefore, considering adverse effects of the stress on pregnancy outcomes, some strategies should be designed and implemented in order to strengthen and improve the social support for pregnant women so that it can reduce the rate of pregnant women's stress.